Penerapan Inovasi Teknologi Pengolahan Hijauan Pakan (Silase) pada Jamaah Tani Muhammadiyah Karanganyar - Ina Nurtanti; Burhan Efendi; Fatihan Akbar (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2025)
Innovations in forage processing technology, especially through the manufacture of silage, are a strategic solution to improve the quality of animal feed in rural communities, including Muhammadiyah farmer groups in Karanganyar Regency. This study aims to analyze the application of silage technology as an alternative to feed forage processing among sheep and cattle farmers in Kedungjeruk Village, Karanganyar. By adopting forage processing technology into silage, it is hoped that it can increase the resilience of animal feed, reduce dependence on commercial feed, and increase livestock productivity in a sustainable manner. The methods used in this study involve training for farmers, the implementation of silage production, and the evaluation of the impact on the success of animal feed and the economy of farmers. The results of the study show that the application of silage technology is able to reduce the waste of forage forage, extend the shelf life of feed, and improving the quality of feed for livestock. Overall, this innovation has succeeded in making a positive contribution to increasing the independence of animal feed and farmers' income in the area, while supporting the development of a circular economy based on agriculture and livestock